2016
DOI: 10.1002/jcp.25450
|View full text |Cite
|
Sign up to set email alerts
|

Browning of White Fat: Novel Insight Into Factors, Mechanisms, and Therapeutics

Abstract: What is more interesting about brown adipose tissue (BAT) is its ability to provide thermogenesis, protection against obesity by clearing triglycerides, releasing batokines, and mitigating insulin resistance. White adipose tissue (WAT) on the other hand stores excess energy and secretes some endocrine factors like leptin for regulating satiety. For the last decade there has been an increasing interest in the browning of fat keeping in view its beneficial effects on metabolic disorders and protection in the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(134 citation statements)
references
References 93 publications
3
127
0
1
Order By: Relevance
“…Our group also demonstrated in a previous study the exercise ability in promoting morphological and molecular alterations in healthy rats, PVAT, associated with increased protein expression of pAMKThr172 and mtTFA. Recently, it has been demonstrated the important role of aerobic exercise training in the browning process of white adipose tissue (WAT) via activation of several pathways including AMPK, PGC‐1α and UCP‐1, but no studies have examined the amount of PVAT in responses to exercise training. Thus, the novelty of our study is to show the importance of aerobic exercise training on PVAT morphological alterations indicating a vascular protective effect in rats fed a high‐fat diet.…”
Section: Discussionsupporting
confidence: 62%
“…Our group also demonstrated in a previous study the exercise ability in promoting morphological and molecular alterations in healthy rats, PVAT, associated with increased protein expression of pAMKThr172 and mtTFA. Recently, it has been demonstrated the important role of aerobic exercise training in the browning process of white adipose tissue (WAT) via activation of several pathways including AMPK, PGC‐1α and UCP‐1, but no studies have examined the amount of PVAT in responses to exercise training. Thus, the novelty of our study is to show the importance of aerobic exercise training on PVAT morphological alterations indicating a vascular protective effect in rats fed a high‐fat diet.…”
Section: Discussionsupporting
confidence: 62%
“…However, RT yielded significantly higher the expression of PGC1-α as well as UCP1 in Ovx-RT. Our results corroborate with the findings of Barbosa, Shiguemoto, et al that also reported lower PGC1-α in Ovx rats and their study showed that the reduction of PGC1-α expression are accompanied by significant reductions in genes and proteins as TFAM and NRF1, which favor mitochondrial biogenesis and also improve the thermogenic machinery [37,[48][49][50]. These data represent an important contribution to understand the relation of exercise, higher mitochondrial biogenesis and thermogenic process as important strategy to prevent the effects of ovariectomy and development of some obesity-related dis-eases.…”
Section: Resistance Trainingsupporting
confidence: 83%
“…BAT on the other hand is largely beneficial, because this tissue consumes energy and clears triglycerides. It is well-known that physical activity limits WAT and promotes BAT production and studies indicate that these metabolic benefits are mediated, at least in part, by myokines[16,17]. Due to their close proximity to muscle cells, iMATs are likely to be an important target tissue for paracrine myokines that influence fat browning such as musclin, a myokine released from muscles during exercise that activates PPARα-dependent browning of WAT[16,17].…”
Section: Introductionmentioning
confidence: 99%